A metal-dielectric 3D-Printable metastructure for the radiation enhancement of electromagnetic band-gap resonator antennas - Ali, Md Yeakub; Lalbakhsh, Ali; Singh, Khushboo; Taheri, Sina Hasibi; Mukhopadhyay, Subhas (Frontiers in Antennas and Propagation, 2025)
This article introduces a planar, highly transmissive, 3-D printable metastructure with a low profile for enhancing the far-field radiation performance of conventional electromagnetic band-gap (EBG) resonator antennas. The proposed near-field phase transforming metastructure (PTM) is developed by employing the near-field phase transformation approach that transforms the non-uniform phase of a conventional EBG resonator antenna into a nearly uniform one and enhances the far-field radiation pattern. The novelty of this paper lies in reducing the height of the phase-transforming structure compared to state-of-the-art structures with better performance. The metastructure’s low profile is realized by incorporating metal inside the dielectric materials. The proposed PTM comprises two types of unit cells made of metal and dielectric material to achieve a wide range of phase coverage. All the phase transforming unit cells used are highly transmitting as their transmission coefficient (|S21|) is greater than −0.77 dB, which increases the aperture efficiency compared to previous designs. Additionally, the proposed metastructure is fully passive and polarization-independent. To achieve the desired performance, the PTM can be realized by using additive manufacturing technologies and exploiting RF-graded 3-D printing filament. The proposed metastructure-based wide-band EBG resonator antenna achieves a peak directivity, aperture efficiency, and 3 dB directivity bandwidth of 21.4 dBi, 54.65%